Voyager - Gabaldon, Diana (Gabaldon, Diana. Outlander novels., 2002)
Time-travelling Claire Randall returns to her own time, pregnant and weary, and resumes her life, but her memories of her eighteenth-century Scottish lover Jamie Fraser will not die, leading her to a desperate decision to return to him.